2021
DOI: 10.1021/acs.jpcc.1c06914
|View full text |Cite
|
Sign up to set email alerts
|

Thermal- vs Light-Induced On-Surface Polymerization

Abstract: On-surface polymerization is a powerful bottom-up approach that allows for the growth of covalent architectures with defined properties using the two-dimensional confinement of a highly defined single-crystal surface. Thermal heating is the preferred approach to initiate the reaction, often via cleavage of halogen substituents from the molecular building blocks. Light represents an alternative stimulus but has, thus far, only rarely been used. Here, we present a direct comparison of on-surface polymerization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Instead of covalent chains, we observed the formation of short organometallic segments. This indicates low mobility of the radicals on the bare metal surface at room temperature, as similarly suggested by experiments with ultraviolet light-induced dehalo-genation [49]. This may also explain formation of organometallic intermediates rather than the covalent products, where bonding with Ag atoms provided by the free adatom gas is kinetically preferred.…”
Section: Discussion and Summarysupporting
confidence: 56%
“…Instead of covalent chains, we observed the formation of short organometallic segments. This indicates low mobility of the radicals on the bare metal surface at room temperature, as similarly suggested by experiments with ultraviolet light-induced dehalo-genation [49]. This may also explain formation of organometallic intermediates rather than the covalent products, where bonding with Ag atoms provided by the free adatom gas is kinetically preferred.…”
Section: Discussion and Summarysupporting
confidence: 56%
“…As an auspicious stimulus for covalent synthesis, light irradiation can induce polymerization reactions at room temperature . Therefore, the long-range ordered molecular assembly can survive during photochemical reactions and benefit the formation of high-quality 2DPs . For instance, Lackinger et al reported the on-surface photopolymerization of 2DP ordered on the mesoscale.…”
Section: Challenges and Strategies In The Study Of 2dps On Surfacesmentioning
confidence: 99%
“…Two-dimensional (2D) molecular self-assembly is of great significance for building preprogrammed structures and patterns on such a scale using the bottom–top approach . The formation of 2D self-assembled nanostructures is a result of thermodynamic equilibrium, affected by temperature, molecular chemical structure, solvent, solution concentration, substrate, , and so on. These factors essentially change the intermolecular interaction and/or molecule–substrate interaction of self-assembly adlayers.…”
Section: Introductionmentioning
confidence: 99%